Multiphase Particle-in-Cell (MP-PIC) Simulation on Fluidization and Reaction Characteristics in an 80 kW Chemical Looping Gasification Unit - Shen, Cong; Guo, Tuo; Hu, Xiude; Guo, Qingjie (Fine Chemical Engineering, 2023)
A numerical simulation study of the 80 kW Chemical Looping Gasification (CLG) pilot plant fuel reactor was conducted using the Computational Particle Fluid Dynamics (CPFD) method to investigate the influence of superficial gas velocity, coal particle size and static bed height on the gas-solid fluidization characteristics in the bed. The results showed that the suitable operating ranges were superficial gas velocity in 0.36~0.48 m/s, coal particle size in 0.3~0.4 mm, and static bed height in 0.6~0.8 m, and the CLG process released gas in the whole bed compared with the cold condition, which could effectively alleviate the uneven pressure gradient distribution. In addition, the working conditions with superficial gas velocity higher than 0.36 m/s, coal particle size higher than 0.35 mm and static bed height higher than 0.6 m are more favorable to the full contact between coal particles, oxygen carrier bed particles and gas phase, thus obtaining a higher carbon conversion rate.